DEVELOPMENT AND VALIDATION OF STABILITY INDICATING HPTLC METHOD FOR THE SIMULTANEOUS ESTIMATION OF TINIDAZOLE AND FLUCONAZOLE AND ITS APPLICABILITY IN MARKETED DOSAGE FORM - K., NETHRA; MOHAMMED Z., SHAIK; J., KAVITHA; R., SEETHARAMAN; S., KOKILAMBIGAI K.; S., LAKSHMI K. (International Journal of Applied Pharmaceutics, 2022)
Objective: The current method is focused on the development and validation of a simple, rapid, precise and robust stability indicating High Performance Thin Layer Chromatography for the simultaneous estimation of anti-infective drugs Tinidazole and Fluconazole in bulk and its pharmaceutical dosage form. The method was tailored to analyse the drugs in their commercial dosage form (tablets) with no interference from ingredients. Methods: Chromatographic separation was performed over precoated TLC plates (60 F254, 20 cm × 10 cm, 250 μm thickness, Merck) via a linear ascending technique using toluene: acetonitrile as the mobile phase in the ratio 6:4 v/v. Detection and quantification was achieved at the isobestic point of the two drugs, which was observed at 263 nm through Spectro-densitometric analysis. Analytical performance of the proposed HPTLC method was validated according to the ICH guidelines with respect to the linearity, accuracy, precision, detection and quantitation limits, robustness and specificity. Results: Tinidazole and Fluconazole were well separated and identified with an Rf value of about 0.46±0.03 and 0.75±0.05, respectively. The calibration curves were linear over a concentration range of 800-1200ng/spot for Tinidazole and 60-90ng/spot for Fluconazole with correlation coefficients (r2) more than 0.998. The above-developed method was validated as per ICH guidelines Q2(R1) and was found to be precise, sensitive, accurate and robust. Conclusion: The validated stability indicating HPTLC method was found to be simple, precise, accurate and sensitive for the concurrent quantification of Tinidazole and Fluconazole in pharmaceutical dosage form and can be released into quality control for regular analysis.